Uganda - Fiscal Policy for Growth : Public Expenditure Review 2007, Volume 2. Main Report - World Bank (Washington, DC, 2012)
Uganda needs to increase infrastructure investments if impressive growth is to continue. But the Budget is showing increasing signs of stress from expenditure pressures and fiscal tightening. Recent increases in employee costs in central Government functions of public administration, justice law and order, defense, prisons and police have deteriorated the composition of the Budget from the perspective of growth. In common with global experience in tight fiscal circumstances, public infrastructure spending is getting squeezed. These expenditure trends suggest a further squeeze on infrastructure and maintenance is inevitable, in which case growth could slow down. This report concerns how should Uganda respond to these fiscal challenges? Whereas there is scope for prudent new concessional borrowing for infrastructure, disbursement rates in infrastructure projects are too low, making it a priority to address constraints to effective spending. As part of a fiscal strategy for growth, Uganda needs in the short to medium-term to rapidly improve revenue performance without taxing key growth sectors, and to shift the composition of spending towards infrastructure. A compositional shift will require deep public sector reforms, early action on postponed reforms to public administration, and a working program to reduce waste and increase the efficiency of public expenditures, including in Poverty Alleviation Fund (PAF) priority sectors and agencies. A reduction in waste and an increase in public sector efficiency will ultimately require more accountability for the delivery of quality public services than is evident in Uganda today. It will also require a much more systematic effort by spending ministries and agencies: a more structured and a much more strategic approach to public service efficiency from the ministry of finance could be built into budget framework papers as well as preparation of the next Poverty Eradication Action Plan (PEAP).